2018
DOI: 10.5588/ijtld.17.0590
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent tuberculosis in the pre-elimination era

Abstract: Recurrent tuberculosis (TB), defined as TB that recurs after a patient has been considered cured, constitutes a challenge to TB control. In low TB burden countries, the underlying causes and consequences of recurrent TB are poorly understood. We conducted a literature review to summarise the evidence of recurrent TB in low-burden settings and to address current gaps in knowledge. We included peer-reviewed publications on studies conducted in countries with an estimated TB incidence of <100 cases per 100 000 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…A review by Rosser et al also indicates that patients cured of a TB episode have a higher risk of TB than those without prior infection. These authors estimated that the TB rate was 31.5 times higher in recurrences than in new TB cases [5].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A review by Rosser et al also indicates that patients cured of a TB episode have a higher risk of TB than those without prior infection. These authors estimated that the TB rate was 31.5 times higher in recurrences than in new TB cases [5].…”
Section: Discussionmentioning
confidence: 98%
“…Other studies performed in areas with a low burden of the disease have concluded that relapses of a prior infection continue to be the most common cause of TB recurrences. Infections with new Mycobacterium tuberculosis strains are possible but infrequent in low endemic areas [5,12,23,25,26]. Nevertheless, two studies conducted in Spain highlight the importance of TB infections in contexts with a low or moderate incidence [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations